Impact of time-varying exposure on estimated effects in observational studies using routinely collected data: protocol for a cross-sectional study - Ling Li; Xin Sun; Jing Tan; Mei Liu; Wen Wang; Kevin Lu; Guowei Li; Jiayue Xu; Jeff Jianfei Guo (BMJ Open)
Introduction Time-varying exposure is an important issue that should be addressed in longitudinal observational studies using routinely collected data (RCD) for drug treatment effects. How well investigators designed, analysed and reported time-varying exposure, and to what extent the divergence that can be observed between different methods used for handling time-varying exposure in these studies remains uncertain. We will conduct a cross-sectional study to comprehensively address this question.Methods and analysis We have developed a comprehensive search strategy to identify all studies exploring drug treatment effects including both effectiveness and safety that used RCD and were published in core journals between 2018 and 2020. We will collect information regarding general study characteristics, data source profile, methods for handling time-varying exposure, results and the interpretation of findings from each eligibility. Paired reviewers will screen and extract data, resolving disagreements through discussion. We will describe the characteristics of included studies, and summarise the method used for handling time-varying exposure in primary analysis and sensitivity analysis. We will also compare the divergence between different approaches for handling time-varying exposure using ratio of risk ratios.Ethics and dissemination No ethical approval is required because the data we will use do not include individual patient data. Findings will be disseminated through peer-reviewed publications.